A Companion to the Intellectual Life of the Palaeologan Period
1 online resource
Keywords: What was happening in Byzantium as the Turks drew ever closer to Constantinople and an interest in classical Greek studies had been rekindled in the West? What was the role of the Byzantine scholars in an Empire facing multiple political and economic problems, and what were the matters that engaged them? What was the importance of teachers, libraries and monasteries to the so-called Palaeologan Renaissance, and what the significance of the theological disputes? These questions and more are addressed in the twelve essays authored by international experts of this Companion, which advances our understanding of the intellectual milieux, trends, and achievements of the Palaeologan period. Contributors are: Giuseppe De Gregorio, Pantelis Golitsis, Eleni Kaltsogianni, Apostolos Karpozilos, Sofia Kotzabassi, Sophia Mergiali-Sahas, Ioannis Polemis, Alexander Riehle, Demetra Samara, Ilias Taxidis, and Ioannis Vassis.